Perioperative medicine in paediatric anaesthesia. (2nd December 2021) - Stokes, Matthew; Sivaprakasam, Jai
Abstract : Perioperative medicine is an expanding field within paediatric surgery. This article gives an overview of the different areas of perioperative medicine throughout the paediatric surgical journey.